Hematological adverse effects and pharmacokinetics of ribavirin in pigs following intramuscular administration. Issue 5 (15th February 2017) - Lee, D.‐U.; Je, S. H.; Yoo, S. J.; Kwon, T.; Shin, J. Y.; Byun, J. J.; Park, J.‐H.; Jeong, K.‐w.; Ku, J.‐M.; Lyoo, Y. S.
Abstract : Ribavirin (RBV) is a synthetic guanosine analog that is used as a drug against various viral diseases in humans. The in vitro antiviral effects of ribavirin against porcine viruses were demonstrated in several studies. The purposes of this study were to evaluate the adverse effects and pharmacokinetics of ribavirin following its intramuscular (IM) injection in pigs. Ribavirin was formulated as a double‐oil emulsion (RBV‐DOE) and gel (RBV‐Gel), which were injected into the pigs as single‐dose IM injections. After injection of RBV, all of the pigs were monitored. The collected serum and whole blood samples were analyzed by liquid chromatography–tandem mass spectrometry and complete blood count analysis, respectively. All of the ribavirin‐treated pigs showed significant decreases in body weight compared to the control groups. Severe clinical signs including dyspnea, anorexia, weakness, and depression were present in ribavirin‐treated pigs until 5 days postinjection (dpi). The ribavirin‐treated groups showed significant decrease in the number of red blood cells and hemoglobin concentration until 8 dpi. The mean half‐life of the RBV‐DOE and RBV‐Gel was 27.949 ± 2.783 h and 37.374 ± 3.502 h, respectively. The mean peak serum concentration (Cmax ) and area under the serum concentration–time curve from time zero to infinity (AUCinf ) of RBV‐DOE were 8340.000 ± 2562.577 ng/mL and 16 0095.430 ± 61 253.400 h·ng/mL, respectively. The Cmax and AUCinf of RBV‐Gel were 15 300.000 ± 3764.306 ng/mL and 207526.260 ± 63656.390 h·ng/mL, respectively. The results of this study provided the index of side effect and pharmacokinetics of ribavirin in pigs, which should be considered before clinical application.